Financial Accessibility and Growth of Smes: A Case Study of Mukono Municipal in Uganda - Kenny Manimani Birindwa (Uganda Christian University, 2024)
This study looked at the relationship between financial accessibility and the expansion of SMEs in Uganda’s Mukono Municipality. The need to comprehend how different financial accessibility issues affect SME growth in the current economic environment was the main subject addressed. The study’s objectives were to appraise the impact of branch networks of financial institutions, investigate the impact of digital banking services, and determine how geographical distribution of financial services affects SMEs’ access to capital. The research design utilized a mixed-methods strategy, which combined qualitative and quantitative data collection methodologies. While surveys were used to collect data on the financial inclusion experience, in-depth interviews with owners and managers of small and medium-sized enterprises were conducted to gain an in-depth understanding. Areas with well-distributed branch networks and access to digital banking services and proximity to financial institutions saw greater levels of financial growth, operational efficiency, and market competitiveness. However, it was observed that full accessibility to financing by SMEs was hindered by aspects such as low financial literacy, high transaction costs, and unequal geographical distribution of financial services. Among recommendations put forward towards improving SME access to finance are utilization of digital banking, expansion of branch networks, and targeted financial literacy campaigns. The conclusion of the study points to how financial accessibility bears highly on SME expansion, while giving recommendations that are achievable to increase access to financial services for the long-term expansion and financial success of SMEs in Mukono Municipality.